2021
DOI: 10.1186/s13014-021-01961-9
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy with a fixed beamline for skull-base chordomas and chondrosarcomas: outcomes and toxicity

Abstract: Aim This study presents an analysis (efficacy and toxicity) of outcomes in patients with skull-base chordomas or chondrosarcomas treated with a fixed horizontal pencil proton beam. Background Chordomas (CAs) and chondrosarcomas (CSAs) are rare tumours that are usually located near the base of the skull and very close to the brain's most critical structures. Proton therapy (PT) is often considered the best radiation treatment for these diseases, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…With new technological advances in the image guidance, patient positioning, beam delivery, etc., the approach is gaining a renewed interest ( 21 ). Our own clinical practice comprises a positive experience of upright PT for similarly complicated tumors including skull base chordomas and chondrosarcomas ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…With new technological advances in the image guidance, patient positioning, beam delivery, etc., the approach is gaining a renewed interest ( 21 ). Our own clinical practice comprises a positive experience of upright PT for similarly complicated tumors including skull base chordomas and chondrosarcomas ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, an escalated dose to the skull base leads to risks of brain necrosis or vision loss [36], and several reports have suggested necrosis of the temporal lobe in particular. Gordon et al treated 31 patients with chordoma or chondrosarcoma with PBT and found 2 cases with Grade 2 or higher temporal lobe necrosis [37]. Similarly, Pehlivan et al used PBT in 62 patients with basilar chordoma or chondrosarcoma and found 7 cases with temporal lobe necrosis, of which 2 were Grade 2 or higher [38].…”
Section: Discussionmentioning
confidence: 99%
“…This allows for the effective sparing of surrounding healthy tissue and organs at risk and thus reducing treatment toxicity. Proton therapy is routinely used for the treatment of various tumor sites [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and is a dynamically developing form of radiotherapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%